1992
DOI: 10.1002/bjs.1800790942
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic approach to Meckel's diverticulectomy

Abstract: Correspondence La pa roscopic append icectomySir I was delighted to read the excellent Leading Article by Messrs Loh and Taylor ( B r J Surg 1992; 79: 289-90). There is no doubt that laparoscopic appendicectomy is often easier than laparoscopic cholecystectomy, provided the right technical approach is learnt and subsequently developed. The difficulty has been that most appendicectomies in this country are performed as an emergency, and in the first few cases the 'learning curve' means that the procedure will t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…However, this procedure had potential inherent risk of leaving behind ectopic epithelium or the peptic ulcers in the adjacent ileal mucosa. In order to circumvent these potential risks, Ng et al [10] described the laparoscopic assisted extracorporeal Meckel's diverticulectomy with endo GIA stapler and side-to-side ileal anastomosis. Further modification of the procedure by way of extracorporeal Meckel's diverticulectomy with hand-sewn anastomosis has been described [3,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this procedure had potential inherent risk of leaving behind ectopic epithelium or the peptic ulcers in the adjacent ileal mucosa. In order to circumvent these potential risks, Ng et al [10] described the laparoscopic assisted extracorporeal Meckel's diverticulectomy with endo GIA stapler and side-to-side ileal anastomosis. Further modification of the procedure by way of extracorporeal Meckel's diverticulectomy with hand-sewn anastomosis has been described [3,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis and management of complicated or incidental MD in children has undergone a sea change in the minimal access era [3][4][5][7][8][9][10][11][12][13][14][15][16][17]. The diagnosis of Meckel's diverticular complications based on the clinical features and conventional radiological modalities is fraught with limitations as MD is a mobile structure and mimics other common conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Segmental bowel resection including the diverticulum with side-to-side anastomosis can be done by laparoscopy either by laparoscopy-assisted or by laparoscopy with intracorporeal suturing and tying or by using Endo LCS stapler [14,23,24]. Attwood et al [25] reported the first laparoscopy-assisted simple-stapler resection of MD and Teitelbaum et al [5] performed Meckel's diverticulectomy completely by laparoscopy using Endo LCS, whereas Ng et al [23] performed laparoscopy-assisted resection of intestine bearing MD with side-to-side anastomosis using an Endo LCS. Altinli [26] performed laparoscopy-assisted wedge excision of MD and transverse closure of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…9 Ng et al reported the extracorporeal resection of MD with staplers and stated that although intracorporeal resection is feasible, it risks intraperitoneal spillage and requires more incisions for bowel clamps. 10 Altinli and coworkers described laparoscopically assisted extracorporeal resection of MD and hand-sewn anastomosis. 1 Laparoscopically assisted transumbilical Meckel's diverticulectomy (LATUM) with hand-sewn anastomosis is the procedure used for management of asymptomatic as well as complicated MD at our institute.…”
Section: Discussionmentioning
confidence: 99%